Bridging the logistics divide with service inclusion for socially sustainable urban logistics services - Altuntas Vural, Ceren; Sanchez-Diaz, Ivan; Halldórsson, Árni; Ait, Linda-Triin (European Journal of Transport and Infrastructure Research, 2024)
The rise of e-commerce over the last decade has increased the pressure on urban logistics and highlighted important sustainability challenges. The COVID-19 pandemic exacerbated this trend and underscored the need to address social sustainability challenges with e-commerce. In particular, the pandemic drew attention to the uneven access to home deliveries and the importance of having a logistic system that is aligned with the principles underlying society and sustainable development goals. The purpose of this paper is to identify urban logistics services that emerged in response to access limitations linked to the COVID-19 pandemic, and to analyse how these services can enhance inclusivity and fair access to goods. We adopt an exploratory and qualitative research design based on a deductive content analysis approach. This method aims to systematize, objectively analyse, and draw assumptions from secondary evidence and semi-structured interviews with key actors. We identified several urban logistics innovations that spanned organizational, transportation modal shift, informational and technological approaches to face existing restrictions. The findings indicate a deficiency in inclusivity and equitable access to logistics innovations, prompting ad-hoc organization by citizens and private initiatives in response to the extraordinary circumstances of the pandemic. We introduced the concept of logistics divide to analyse the inequalities on who benefits from logistics innovations. This divide is a consequence of the uneven ability of different consumer segments to get access to those services either due to digital mastery, geographical barriers, legal barriers, or to economic reasons. The findings also showed that urban logistics actors have started to innovate to increase access to goods after the pandemic disclosed this logistics divide. In essence, this paper shows the importance of integrating transport and logistics research with transformative service research to decrease the logistics divide and achieve more equitable urban logistics.